Findings of ancient coins in Kuyavia and Pałuki in the collections of The Leon Wyczółkowski District Museum in Bydgoszcz and in the light of its archivies - Frischke, Gabriela; Jarzęcki, Krzysztof (Acta Archaeologica Lodziensia, 2024)
The article presents an analysis of ancient coin finds from the Kuyavia and Pałuki regions, currently held in the collections of the Historical Society in Bydgoszcz, later inherited by the Leon Wyczółkowski District Museum, or recorded in the archival documentation of these institutions. The verification process included not only entries in various inventory ledgers and documents but also scholarly literature, where errors were often repeated by subsequent authors. As a result, the article offers resolutions to conflicting records, provides a comprehensive list of ancient coins discovered in the mentioned areas, and expands knowledge regarding their acquisition for the Society’s and Museum’s collections. It also traces the subsequent history of these coins in the collections of Bydgoszcz institutions, indicating which of them should be classified as wartime losses.